Literature Review Study: Factors That Influence Customer Satisfaction - Muphimin, Muphimin; Syahril Djaddang (Jurnal Ekonomi, 2024)
Satisfaction can be defined as a person's feeling of satisfaction, pleasure and relief due to consuming a product or service. Satisfaction level is a function of the difference between perceived performance and expectations. If performance is below expectations, then consumers will be very disappointed, if performance meets expectations then consumers will be very satisfied. This research uses the literature review method, which is an explanation of theories, findings and other research sources taken from references to become the basis for conducting research. Based on theory, relevant articles and discussions, a hypothesis can be formulated for further research: That if customers give good perceptions of quality, product, price, service quality, emotional factors, customer relationship management, service quality, and word of mouth, then This will have a positive effect on consumer satisfaction.